Efficacy of Carrageenan as Emulsifier and Breadfruit Flour as Substitute Ingredient on Physicochemical, Microbial and Organoleptic Properties of Fermented Ice Cream - Minh Phuoc Nguyen (Journal of Global Pharma Technology, 2016)
Breadfruit is a nutritious food but not widely utilized in industrial production. Carrageenan has excellent functionality on phase separation and cryoprotection. Ice cream is a delicious and nutritious frozen dairy product widely consumed. It is a complex microcrystalline network of liquid and solid phases. This study focused on the utilization of carrageenan as stabilizer and breadfruit flour as a substitute ingredient on physicochemical, microbial and organoleptic properties of fermented ice cream. Different supplementation ratio of carrageenan (0.5%, 1.0%, 1.5%, 2.0%, 2.5%) and breadfruit: milk (30%:, 70%; 40:60%, 50%:50%, 60%: 40%; 70%: 30%) were demonstrated. The fermentation process was conducted with Lactobacillus sp. starter culture (ratio 0.2%) at loading cell 109 cfu/ml at 37oC in 48 hours. Results revealed that carrageenan (2.0%), breadfruit: milk (60%: 40%) were ideal for production of fermented ice cream. From this investigation, consumers have more chance to consume one kind of functional ice cream from breadfruit starch.Keywords: Breadfruit, Carrageenan, ice cream, Lactobacillus, physicochemical, Microbial, Organoleptic, fermentation.